2021
DOI: 10.1002/aelm.202001080
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐Phase Exfoliated Gallium Selenide for Light‐Driven Thin‐Film Transistors

Abstract: Gallium selenide (GaSe), a layered semiconductor of Group‐III monochalcogenides, has been recognized by the scientific community in recent years as an appealing material in the fields of photonics and (opto)electronics. Thanks to its pseudodirect bandgap and its thickness‐dependent (opto)electronic properties, GaSe has emerged as a promising candidate for the implementation of thin‐film transistors (TFTs) and photodetectors with fast response and high sensitivity. Solution processing of 2D materials provides l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 158 publications
(232 reference statements)
0
24
0
Order By: Relevance
“…[ 62,65–67 ] In order to estimate the light‐detection performance of the two systems, the photoresponsivity ( R ph ), defined as the efficiency in converting the optical signal into an electrical one, represents a fundamental figure of merit. We calculated R ph of both devices given by: [ 62,65,68 ] Rphbadbreak=IphIr·S\[ \begin{array}{*{20}{c}}{{R_{{\rm{ph}}}} = \frac{{{I_{{\rm{ph}}}}}}{{{I_{\rm{r}}}\cdotS}}}\end{array} \] in which I r is the irradiance, S is the active area of the device. We found that the maximum measured responsivity for both devices is achieved at the lowest irradiance (≈10 mW cm –2 ) for both the ML‐MoSe 2 device ( R ph ≈ 9 A W −1 ) and the HET device ( R ph ≈ 88 A W −1 ) and decreases with the increase of irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 62,65–67 ] In order to estimate the light‐detection performance of the two systems, the photoresponsivity ( R ph ), defined as the efficiency in converting the optical signal into an electrical one, represents a fundamental figure of merit. We calculated R ph of both devices given by: [ 62,65,68 ] Rphbadbreak=IphIr·S\[ \begin{array}{*{20}{c}}{{R_{{\rm{ph}}}} = \frac{{{I_{{\rm{ph}}}}}}{{{I_{\rm{r}}}\cdotS}}}\end{array} \] in which I r is the irradiance, S is the active area of the device. We found that the maximum measured responsivity for both devices is achieved at the lowest irradiance (≈10 mW cm –2 ) for both the ML‐MoSe 2 device ( R ph ≈ 9 A W −1 ) and the HET device ( R ph ≈ 88 A W −1 ) and decreases with the increase of irradiation.…”
Section: Resultsmentioning
confidence: 99%
“… 4 A single layer of β-GaS is composed of S–Ga–Ga–S repeating units, with different layers kept together along the c -axis by weak van der Waals forces. 7 , 8 Differently from other investigated transition-metal monochalcogenides (e.g., GaSe, 9 , 10 InSe, 11 , 12 GeSe, 13 and SnSe 14 ), the bulk form of GaS has a large optical band gap ( E g ) (at 300 K: indirect E g ∼ 2.5 eV; 15 18 direct E g ∼ 3.0 eV 17 19 ). The E g drastically increases above 3 eV with decreasing thickness down to the monolayer state due to quantum confinement effects.…”
Section: Introductionmentioning
confidence: 89%
“…Gallium sulfide (GaS) is a binary IIIA–VIA group compound, which has gained increasing attention among the plethora of layered semiconductors due to its distinctive optoelectronic and anisotropic structural properties. Depending on the stacking of layers, four GaS polytypes (β, ε, γ, and δ) are distinguished, although the hexagonal (2H phase) β-polytype , is the most energetically favorable crystal arrangement . A single layer of β-GaS is composed of S–Ga–Ga–S repeating units, with different layers kept together along the c -axis by weak van der Waals forces. , Differently from other investigated transition-metal monochalcogenides (e.g., GaSe, , InSe, , GeSe, and SnSe), the bulk form of GaS has a large optical band gap ( E g ) (at 300 K: indirect E g ∼ 2.5 eV; direct E g ∼ 3.0 eV ). The E g drastically increases above 3 eV with decreasing thickness down to the monolayer state due to quantum confinement effects. , Therefore, two-dimensional (2D) GaS fills the void between 2D small- E g semiconductors and insulators, which is of interest for the realization of ultraviolet (UV)-selective photodetectors, color-tuneable blue/UV light-emitting diodes (LEDs), and van der Waals type-I heterojunctions in photocatalysis. , Meanwhile, 2D GaS emerged as a potential material for applications such as electrochemical water splitting, hydrogen storage, energy storage (e.g., Li-ion batteries), , gas sensing, , DNA sequencing, and nonlinear optics. , Contrary to several 2D materials, which are reactive to air (e.g., elemental analogue of graphene, such as silicene, germanene, and stanene , as well as transition-metal tellurides , ) or undergo photoinduced oxidation (e.g., phosphorene and metal monochalcogenides such as GaSe …”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, GaSe combines the advantages of 2D structures for detection within the visible spectrum, with an easier route to integration with conventional silicon integrated circuits. Several GaSe-based photodetectors have been demonstrated in the past years ,, and in 2020, Sorifi et al and Tan et al published very promising results showing responsivities of 2.6 and 3000 A/W and detectivities of 1 × 10 12 Jones and 1 × 10 13 Jones, at 380 and 405 nm, respectively. , Despite those first demonstrations, many challenges still have to be overcome to fabricate reliable devices, among them, the elaboration of single-crystal 2D materials on large scale using methods compatible with existing silicon technologies. An alternative to forming continuous 2D layers is to explore one-dimensional objects with good materials quality.…”
Section: Introductionmentioning
confidence: 99%